The Efficacy of Oral/Intravenous Corticosteroid Use in COVID-19 Patients: A Systematic Review - Latarissa IR; Rendrayani F; Iftinan GN; Suhandi C; Meiliana A; Sormin IP; Barliana MI; Lestari K (Dove Medical Press, 2024)
Irma Rahayu Latarissa,1,2 Farida Rendrayani,1 Ghina Nadhifah Iftinan,2 Cecep Suhandi,3 Anna Meiliana,1,4 Ida Paulina Sormin,5,6 Melisa Intan Barliana,7,8 Keri Lestari1,2,8 1Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, Indonesia; 2Medication Therapy Adherence Clinic (MTAC), Universitas Padjadjaran, Sumedang, Indonesia; 3Department of Pharmaceutical Analysis and Medicinal Chemistry, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, Indonesia; 4Prodia Clinical Laboratory, Central Jakarta, Indonesia; 5Faculty of Pharmacy, University of 17 August 1945 Jakarta, Jakarta, Indonesia; 6Prodia Diacro Laboratories, Jakarta, Indonesia; 7Department of Biological Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, Indonesia; 8Center of Excellence for Pharmaceutical Care Innovation, Universitas Padjadjaran, Sumedang, IndonesiaCorrespondence: Keri Lestari, Department of Pharmacology and Clinical PharmacyFaculty of Pharmacy, Universitas Padjadjaran, Jl. Raya Bandung Sumedang KM. 21, Jatinangor, 45363, Indonesia, Email lestarikd@unpad.ac.idAbstract: The COVID-19 pandemic is prompting extensive investigation into potential treatments, including the use of corticosteroids to manage inflammation and mitigate severe disease outcomes. Therefore, this systematic review aimed to evaluate the efficacy of oral/intravenous corticosteroids in the management of COVID-19. A comprehensive search was conducted across major scientific databases such as MEDLINE, Scopus, and Cochrane for relevant studies published from 2019- 2024. The inclusion criteria included studies investigating the use of oral/intravenous corticosteroids in COVID-19 patients > 18 years with a randomized placebo-controlled trial method. Non-placebo-controlled studies, studies using combined treatments with other drugs, as well as protocol articles, conference proceedings, review articles, and non-English studies were excluded. A narrative synthesis approach was adopted given the significant methodological diversity. The results showed that a total of 12 studies met the inclusion criteria covering the use of three drugs, including dexamethasone (three), hydrocortisone (two), and methylprednisolone (seven). The outcome parameters used for each study were different. Among the total 12 studies, five showed insignificant results for hydrocortisone (two) and methylprednisolone (three), while others reported significant results. This systematic review suggested that oral/intravenous corticosteroids might confer clinical benefits in the management of COVID-19, particularly in reducing mortality and severe disease outcomes. However, further investigation was needed to establish standardized protocols regarding dosage, duration, and safety considerations to optimize efficacy and minimize potential adverse effects.Keywords: efficacy, corticosteroid, SARS-CoV-2, randomized controlled trial, clinical trial